IMMU-22. TARGETING NON-CANONICAL FUNCTION OF IDO1 IN GLIOBLASTOMA IMMUNOTHERAPY. (11th November 2019) - Zhai, Lijie; Bell, April; Qian, Jun; Ladomersky, Erik; Lauing, Kristen; Wainwright, Derek
Abstract: Recent failure of immune checkpoint blockade, anti-PD-1 therapy in patients suffering recurrent glioblastoma (GBM) indicates that development of novel immunosuppressive mediator-targeted therapeutic strategy is critical for more effective immunotherapies against GBM. Indoleamine 2, 3-dioxygenase 1 (IDO1) has been shown to mediate tumor-induced immunosuppression through its tryptophan catabolic activity. Surprisingly, pharmacological IDO1 enzyme inhibitors have not demonstrated any survival benefit in cancer patients either mono-therapeutically or in combination with other therapies. Previously we confirmed that tumor IDO1 mRNA expression is significantly upregulated in GBM patients compared to those from patients with lower grades gliomas. Furthermore, knockdown of IDO1 in mouse GBM cells significantly increased mouse survival and decreased tumor infiltrating Tregs, but did not affect tumor local tryptophan catabolism. Consistently, inhibition of IDO1 enzymatic activity on GBM-bearing mice did not yield any survival benefit. These findings indicate that IDO1 may suppress immune response through a non-enzymatic pathway. To test this hypothesis, IDO1-deficient mouse GBM cells were created and modified to stably express either wild-type (WT) or enzyme-null IDO1. Syngeneic mice intracranially engrafted with both WT and enzyme-null IDO1 overexpressing GBM cells showed significantly increase of tumor infiltrating Tregs and decreased survival in comparison to mice engrafted with IDO1-deficient GBM cells. In contrast, no difference was observed between WT-IDO1 GBM and enzyme-null IDO1 GBM groups. Additionally, when co-cultured with splenic monocytes, both WT and enzyme-null IDO1 overexpressing GBM cells induced more mature macrophages than IDO1-deficient GBM cells. Taken together, our data strongly imply an enzyme independent pathway associated with IDO1-driven immunosuppression in mouse GBM. Validation of this novel mechanism on human GBM cells is ongoing. A soluble molecule has been identified as a potential mediator for the non-enzymatic function of IDO1. Results from this study will provide innovative strategies for IDO1-based immunotherapy against GBM.